Legal Position of Land in the Agrarian Law and its Implications for National Development - Zainudin Hasan; Putra, Erico (Terekam Jejak Publisher, 2024)
Agrarian law in Indonesia is an important part of the national legal system which regulates the use and control of land, water, space and the natural resources contained therein. As the main basis, the Basic Agrarian Law (UUPA) Number 5 of 1960 provides the legal basis for land rights, including Land Control Rights (HPAT), which reflects authority in the use and management of land. Land law in Indonesia consists of written and unwritten provisions, including customary law which still applies in land tenure practices. This research uses a normative juridical approach with analysis of secondary data originating from statutory regulations, books and journals related to agrarian law and land law. The research results show that agrarian law has a strategic role in ensuring social justice and community welfare, especially in the context of agrarian reform which seeks to overcome inequality in land ownership due to the legacy of colonialism. By providing legal certainty over land rights, agrarian law can contribute to sustainable national development, create socio-economic stability, and improve the welfare of the Indonesian people.